Pengaruh Multiply Card terhadap Hasil Belajar Perkalian Siswa Kelas II SDN 08 Sungai Raya. - Sima; Afryaningsih, Yunika; Purwaningsih , Dewi Ismu (SM Institute, 2025)
This research aims to present data on the influence of multiply cards learning media on the multiplication learning outcomes of class II students at SDN 08 Sungai Raya. The research method used is the experimental method, while the research design used is quasi experimental design. The independent variable (X) in this research is the influence of multiply cards, while the dependent variable (Y) is student learning outcomes. The population included in this research were students in class II A as the experimental class and class II B as the control class at SDN 08 Sungai Raya. Class II A has 25 students consisting of 15 male students and 10 female students. Meanwhile, class II B has 25 students consisting of 14 male students and 11 female students. The samples in this study were students of class II A, experimental class) and II B (control class) at SDN 08 Sungai Raya. The technique used to determine the experimental class and control class uses simple random sampling. In data collection, researchers used test questions. Hypothesis testing uses the t-test formula (paired samples t-test) which is preceded by prerequisite analysis tests, namely the normality test and homogeneity test. The research results showed that there was a significant difference in student learning outcomes between the experimental class and the control class using multiply cards and the control class without multiply cards. This is shown by the t-test results, the significance value obtained using the Paired Samples T Test (Sig) is 0.000 < 0.05, so it can be concluded that the Ha data is accepted and H0 is rejected. This means that there is a significant influence of the use of multiply cards on the multiplication learning outcomes of class II students at SDN 08 Sungai Raya for the 2023/2024 academic year. This data is supported by a comparison of the average value of student learning outcomes in the experimental class which is greater than the control class, namely 77 > 70.6. Keywords : Multiply cards learning media; student learning outcome s